2013
DOI: 10.1128/iai.01165-12
|View full text |Cite|
|
Sign up to set email alerts
|

The Type VI Secretion System Encoded in Salmonella Pathogenicity Island 19 Is Required for Salmonella enterica Serotype Gallinarum Survival within Infected Macrophages

Abstract: Salmonella enterica serotype Gallinarum is the causative agent of fowl typhoid, a disease characterized by high morbidity and mortality that causes major economic losses in poultry production. We have reported that S. Gallinarum harbors a type VI secretion system (T6SS) encoded in Salmonella pathogenicity island 19 (SPI-19) that is required for efficient colonization of chicks. In the present study, we aimed to characterize the SPI-19 T6SS functionality and to investigate the mechanisms behind the phenotypes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 70 publications
0
46
1
5
Order By: Relevance
“…The level of replication for the wt observed in this assay is similar to the level others have reported (Blondel et al, 2013). In contrast to observation in S. Typhimurium (Jelsbak et al, 2012), these results indicate that intracellular replication of S. Gallinarum is not affected by polyamines (Fig.…”
Section: Polyamines Are Not Required For Intracellular Survival and Rcontrasting
confidence: 41%
“…The level of replication for the wt observed in this assay is similar to the level others have reported (Blondel et al, 2013). In contrast to observation in S. Typhimurium (Jelsbak et al, 2012), these results indicate that intracellular replication of S. Gallinarum is not affected by polyamines (Fig.…”
Section: Polyamines Are Not Required For Intracellular Survival and Rcontrasting
confidence: 41%
“…1), and for S. Gallinarum and S. Pullorum, the retention of a functional SPI-19 is consistent with the T6SS it encodes being important for S. Gallinarum survival in chicken macrophages (16). However, the degradation of SPI-6 and loss of the T6SS, seen within the second clade of S. Enteritidis and the S. Gallinarum/S.…”
Section: Resultsmentioning
confidence: 94%
“…SPI-19 is necessary for survival of Salmonella Gallinarum inside avian macrophages, without contributing to cytotoxicity and cell death (26). Since SPI-19 of Salmonella Enteritidis lost many of the T6SS essential components, it was suggested that this system is not functional within this serotype (27).…”
Section: Resultsmentioning
confidence: 99%